Surgical Indications in 22 Patients with Hepatic Portal Venous Gas - Kai, Masahiro; Nanashima, Atsushi; Kai, Kengo; Tanaka, Shunichi (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2019)
The subjects were 22 patients with hepatic portal venous gas (HPVG) findings who were treated at our hospital. We compared Group A, in which surgery was ultimately indicated (including preoperative deaths), with Group B, which received successful conservative treatment. We then examined the surgical indications for patients with HPVG in the emergency room. CT findings such as extrahepatic portal venous gas (85.7％ vs. 25.0％, P＝0.0083), pneumatosis intestinalis (64.3％ vs. 12.5％, P＝0.0310), and ascites (78.6％ vs. 25.0％, P＝0.0260) were significantly more common in Group A. The appearance of extrahepatic portal venous gas, pneumatosis intestinalis, and ascites on CT findings might be important objective indicators of a need for surgery in patients with HPVG.